La lógica de Hegel y la totalidad emergente - Corona Fernández, Javier (2014)
This paper exposes the category of totality in Hegel’s Science of Logic. It’s discursive strategy consists in exposing the key of the vault of Hegel’s idealism: the identity between being and thinking, which unlike Saint Anselm, is a historical and cultural construction whose main character is the subject.